Development of Interactive Powerpoint-Based IPAS Learning Media on the Material of Plant Sources of Life on Earth for Class IV SD Negeri Tugurejo 02 Semarang City - Marsya Fatkhia Nurani; Dewi Nilam Tyas (Jurnal Penelitian Pendidikan IPA, 2024)
This study was conducted to develop, test the feasibility and effectiveness of interactive powerpoint-based IPAS learning media on the material of Plant Sources of Life on Earth to improve student learning outcomes. This research uses the ADDIE model. The sampling technique used nonprobability sampling technique, namely purposive sampling. Data collection techniques through tests and non-tests. The results of the product validation test by media expert validators obtained a percentage of 93.3% in the "Very Feasible" category and through material expert validators obtained a percentage of 92% in the "Very Feasible" category. This is reinforced by the responses of teachers and students in the product trial obtained a percentage of 100% in the "Very Feasible" category. Through the paired sample t-test test shows a sig value. (2-tailed) 0.000 is smaller than 0.050 so that the learning outcomes on the pretest and posttest are significantly different and the N-Gain Test shows a value of 0.69 and 0.65 which is included in the "Moderate" category. It can be concluded that through this research, an interactive powerpoint-based learning media has been developed which is feasible and effective to improve the learning outcomes of fourth class students of SD Negeri Tugurejo 02 Semarang City